Quality of Care for Type 2 Diabetic at José Antonio Echeverría Polyclinic - Lisbeth Fernández González; Armando Rodríguez Salvá; Armando Humberto Seuc Jo; Addys Díaz Piñera (Universidad de las Ciencias Médicas de Cienfuegos, 2019)
Foundation: type 2 diabetes mellitus is the most common diabetes in Cuba, which demands an increase in health services, a situation which could affect the quality of care of these patients. Objective: to evaluate the quality of medical care provided to patients with type 2 diabetes in the José Antonio Echeverría polyclinic, in the Cárdenas municipality in 2016. Method: an investigation was carried out on evaluative health systems and services. A sample was calculated and 375 patients were studied, a stratified two-stage cluster sampling was used for the selection. The variables studied were related to the attention and perception of the patients. The instruments applied were built and validated by experts. The processing was carried out by means of the statistical package SPSS version 21.0. Results: the most distant results from the established standards were found in body mass index, only 29, 6 % had normal weight, users satisfaction (52,5 %), and glycemic control (58,1 %). Conclusions: the quality of care was evaluated as unsatisfactory; the results were evaluated as not acceptable. Despite the existence of national guidelines for the clinical control of the diabetic, these are not always met, as confirmed by the number of uncontrolled patients and dissatisfied with the care received.